Correction: Ulman-Macón et al. Morphological Changes of the Suboccipital Musculature in Women with Myofascial Temporomandibular Pain: A Case-Control Study. Life 2023, 13, 1159 - Daniel Ulman-Macón; César Fernández-de-las-Peñas; Santiago Angulo-Díaz-Parreño; José L. Arias-Buría; Juan A. Mesa-Jiménez (Life)
Error in Figures [...]